Angiotensin converting enzyme 2 (ACE2) - the major receptor for SARS-CoV-2 virus - Sonia Frankowska; Karolina Zając; Klaudia Zargaryan; Jolanta Barbara Zawilska (Polish Pharmaceutical Society, 2021)
The renin-angiotensin-aldosterone system (RAS) plays a significant role in the regulation of the water and electrolyte balance. Renin from the kidneys converts angiotensinogen to angiotensin I. Angiotensin converting enzyme (ACE) catalyzes the conversion of angiotensin I to angiotensin II. The activation of AT1 receptors by angiotensin II causes vasoconstriction, an increase in aldosterone secretion, and an increase in the reabsorption of sodium ions in nephrons, leading to elevation of the blood pressure. Angiotensin II promotes oxidative stress, growth and proliferation of cells, stimulates coagulation, inhibits fibrinolysis, and intensifies inflammatory processes. The ACE-angiotensin II-AT1R pathway is balanced by angiotensin converting enzyme 2 (ACE2), which degrades angiotensin I to angiotensin (1-9) and angiotensin II to angiotensin (1-7). Angiotensin (1-7) and angiotensin (1-9) pathways exert protective effects by activating, respectively, Mas and AT2 receptors. ACE and ACE2 also have intimate roles with the plasma kallikrein-kinin system (KKS), a hormonal pathway that modulates the intrinsic blood coagulation system, endothelial cell growth and angiogenesis, the complement pathway and RAS. The appearance in Wuhan, China, of the first cases of SARS-CoV-2 infections at the end of 2019 launched a series of intensive studies, which proved that the virus invades host cells using ACE2 as a specific receptor. This survey presents basic information on the structure and tissue distribution of ACE2 and the role this enzyme plays in pathogenesis of COVID-19. A particular emphasis is given to pathophysiological effects of the functional superiority of the ACE → angiotensin II → AT1 receptor axis over the pathway ACE2 → angiotensin II → angiotensin (1-7) → Mas receptor. Such disharmony is a consequence of SARS-CoV-2 induced ACE2-downregulation. In the era of the expanding COVID-19 pandemic, intensive research is conducted not only on vaccines and antiviral drugs, but also on compounds that can restore the functional balance between angiotensin II and angiotensin (1-7).